Winter nutrition of spring calving cows on Flint Hills range - Davis, Duane L.; Schalles, R.R.; Drake, C.L.; Kiracofe, G.; Brent, B.E.; McKee, M.; Evans, Jack (Kansas State University. Agricultural Experiment Station, 2011)
Energy appears to be the limiting factor in the rations studied. Three lbs. of milo was superior to 1 1/2 lbs. of soybean meal when date of breeding was considered. In the second trial 3 lbs. of alfalfa and 6 lbs. of milo was superior to 3 lbs. of alfalfa hay and 3 lbs. of milo. Delaying feeding grain until after calving did not give satisfactory results. Possibly additional energy was supplemented too late to be effective.
Keywords: Beef; Soybean meal; Milo; Breeding